The impact of online learning on students learning motivation - Andrian Riyadi; Sudiyatno Sudiyatno (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2023)
The current Covid-19 pandemic forces the learning process to be carried out online or long distance to impact every factor that supports smooth learning, one of which is student learning motivation. Thus, this study aims to determine the impact of online learning on vocational school students' learning motivation. The method used in this study is a qualitative descriptive research method. The research approach used is a literature study by collecting data from the results of research that has been done previously that discusses the variables related to this research. The study indicates that several factors cause a decrease in student learning motivation, including the need for more learning facilities to support student learning activities, including electronic devices and inadequate Internet networks. Boredom is also another factor that reduces students' learning motivation. In addition, changing the method of delivering learning materials to giving individual assignments is a burden for students. The role of the teacher as a motivator and mentor for students in learning could be more optimal, which also causes a decrease in student learning motivation. Parents who are busy and need more time to pay attention to their children's learning conditions also reduce students' learning motivation.